Emulsion copolymerization of vinyl chloride with poly (ethylene glycol) methyl ether methacrylate - Ye Jia; Lijun Fan; Changtong Song; Dong Chen; Xianhong Zhang; Yuhong Ma; Wantai Yang (Designed Monomers and Polymers, 2023)
In this work, we reported a novel emulsion copolymerization of vinyl chloride monomer (VCM) with amphipathic monomer poly (ethylene glycol) methyl ether methacrylate (PEGMA) by using sodium dodecyl sulfate (SDS) as emulsifier and K2S2O8/NaHSO3 as redox initiator. Owing to the multifunctionality of PEGMA that can serve as co-monomer and ‘emulsifier’, the emulsion copolymerization is achieved successfully and the interesting results demonstrate quite different features such as:(1) the stable P[(VC)-co-(PEGMA)] latex is obtained only when the mass ratio of PEGMA > 10% (to total monomer mass), (2) a small amount of ionic emulsifier SDS is required to achieve a stable latex, and (3) the mechanism of the micellar formation is different from the typical emulsion polymerization. Unexpectedly, the obtained copolymer formed high content of gel fraction which is mainly caused by the chain transfer reaction of the PVC growth chain radical to the hydrogen atom of the methylene from alkoxy (-OCH2CH2-) of the PEGMA oligomer chain. However, it could be inhibited effectively by the addition of chain transfer agent 2-mercaptoethanol (2-MCE). Subsequently, the properties of as-obtained P[(VC)-co-(PEGMA)] copolymer are evaluated carefully and it exhibited unique features such as self-plasticization, lower Tg (decreased from 83.1 to 59.6 °C), higher heat resistance (increased from 270 to 290 °C), hydrophilic, and high transparent in comparison to pure PVC. These outstanding features of the P[(VC)-co-(PEGMA)] copolymer offered a potential route for the functional modifications of PVC and broadened its further use.